Visual Design to Support the Sundanese Princess Digital Campaign at the Living Museum of the Kaoetamaan Istri Bandung School - Ghifari, Asy Syifa Rahma; Soewardikoen, Didit Widiatmoko; Azhar, Hanif; Rahman, Yanuar (Sahabat Publikasi, 2025)
The increasing public interest in historical and cultural tourism encourages the need for an attractive digital approach to support the preservation of cultural heritage. The Living Museum of Sakola Kaoetamaan Istri aims to increase public awareness of the history of Indonesia's first women's school as well as become an educational space for Sundanese cultural values. This museum is located in the cultural heritage building of the Dewi Sartika Foundation Elementary and Junior High School in Bandung City. This research aims to design visual support for digital campaigns to increase public awareness and understanding of Sundanese princess culture fought for by the national hero, Dewi Sartika. The design thinking approach used includes the stages of empathize, define, ideate, prototype, and test. The empathize and define stage was carried out through interviews, field observations, and literature studies, with data mapping using the 360 mapping method and SWOT analysis. The ideate and prototyping stage involved 8 tourists and 5 stakeholders in a brainstorming session and design selection. In the test stage, the digital poster mockup was evaluated by 54 respondents through a google form questionnaire based on the Gestalt principle . The digital poster developed contains information about the museum's tour guide services through social media as part of the campaign strategy. The poster visual is presented in the form of a mockup to provide a clear picture to stakeholders and potential visitors regarding the final appearance. The results of the evaluation showed that the majority of respondents understood the message well thanks to a combination of visual elements such as color, layout, font size, illustrations, and supporting photos. The consistency of the visual appearance improves readability, builds the atmosphere of the old women's school, and creates an emotional closeness with visitors. The design of this poster is expected to be a digital campaign model for other living museums in Indonesia.